STUDY OF FLOOD VULNERABILITY CLASS AND MAP IN THE KRUENG JREUE SUB-DAS, ACEH BESAR - Eka Sri Wulandari; Cut Maila Hanum (Jurnal Penelitian Progresif, 2024)
The increasing intensity of land conversion in the Krueng Jreue Aceh Besar Sub-watershed due to changes in land use causes changes in the biophysical characteristics of the land. Changes in the biophysical characteristics of land cause an increase in the level of flood vulnerability. This research uses a descriptive method (survey). The research results show: The variables determining the level of flood vulnerability are based on the biophysical aspects of the land, namely: dynamic factors (rainfall, land use) and static factors (soil infiltration, slope slope). Flood Vulnerability Level Classes and Maps (TKB), consisting of: Very Vulnerable, residential areas, rice fields (42≤TKB≤50); Vulnerable, moor (34≤TKB≤41); and Medium, open land, shrubs, grasslands, secondary forests, primary forests (26≤TKB≤33), average 32.38 (medium class).Primary forests and secondary forests in non-cultivation areas, covering an area of ​​12,598.00 ha or 54.26% of the total area of ​​the Krueng Jreue Sub-watershed (23,218.06 ha), have the lowest level of flood vulnerability. Flood disasters occur in November-December, when rainfall is high, which causes residents to be exposed, physical and economic losses and land damage.